The Implementation of Ice Breaking to Increase Students Motivation in English Learning at Yamueti Kokoda - Siti Tamamala; Agus Setiawan; Nursalim Nursalim (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2020)
This research was conducted in order to see the effect of the implementation of ice breaking to increase students motivation at 7th grade of MTs Yamueti Kokoda. In conducting this research, the rsearcher used pre-experimental design. The researcher used one class in this research. In the class researcher applied pretest and posttest. The sample are the students at 7th grade consisted of 11 students. The results of the research that used ice breaking technique that could be seen the value was lower than a value (0.00 < 0,05), it could seen p value (0,003) and the signifficant level (0,05), the value of fto tally (15,444) was more than ftable (4,96). This mean that an alternative hypotesis there is an influence the implementation of ice breaking on students motivation in english learning (H1) was accepted and, of course a null (H0) was rejected. In other words ice breaking gave the significant influence to the students motivation at 7th of MTs Yamueti Kokoda.